Triglyceride levels and its association with all-cause mortality and cardiovascular outcomes among patients with heart failure - Qing-Wen Ren; Tiew-Hwa Katherine Teng; Wouter Ouwerkerk; Yi-Kei Tse; Christopher Tze Wei Tsang; Mei-Zhen Wu; Hung-Fat Tse; Adriaan A. Voors; Jasper Tromp; Carolyn S. P. Lam; Kai-Hang Yiu (Nature Communications)
Abstract Remnant cholesterol, identified by triglyceride-rich lipoprotein, is a significant causal risk factor for ischemic heart diseases. The association of triglyceride levels with all-cause and cause-specific outcomes in heart failure (HF) remains unexplored. Using a previously validated territory-wide clinical information registry, all eligible patients diagnosed with HF (N = 127124) from 2000 to 2020 were included. In this population-based cohort (mean age: 71.4 ± 12.2 years, 51.8% male), the association between triglyceride levels and risk of all-cause mortality and cardiovascular disease was a U-shapedḍ curve. High triglyceride levels (≥3.0 mmol/L) were associated with atherosclerotic cardiovascular disease admission or death; conversely, lower triglyceride levels (<1.2 mmol/L) were associated with higher risks of HF readmission or death. The risk of adjusted all-cause mortality reached a nadir between triglyceride levels of 1.2 mmol/L and 3.0 mmol/L. Results were externally validated in BIOSTAT-CHF. Our findings have important implications for defining the role of triglyceride levels in contributing to the diverse outcomes in patients with HF.